ANALISIS PROFITABILITAS USAHA PETERNAKAN AYAM PETELUR DI SUYATNO FARM DESA KALISIDI KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Muhammad Luqman Maliki; A Setiadi; W Sarengat (MEDIAGRO, 2017)
A study aims to determine the profitability on a farm chicken laying in suyatno farm. This study implemented at Suyatno Farm in Kalisidi Village, West Ungaran District, Semarang Regency. The data collection in this research using the interview and observations. The kind of data collected is the primary data and data secondary. The data primary in the form of the data “time series” for 3 years of the period of the production of 2013, 2014 and 2015. A quantitative analysis tested using one sample t-test, to comparing the income against the minimum wage districts semarang. Based on research resultsare known to the cost of production Suyatno Farm for 2013-2015 reached the value of Rp 4.709.516.166; Rp 5.884.173.436; Rp 5.826.582.168. A total of acceptance in 2013 reached Rp 6.635.458.237, having an increased to Rp 6.994.021.429 in 2014 and increased to Rp 7.480.983.226 in 2015. The income clean farms Suyatno farm in 2013 reached Rp 1.441.248.738, in 2014 1.087.466.841 and in 2015 Rp 1.376.039.449. The value of income clean experienced a decrease in the 2013-2014, while in the 2014-2015 increased. Based on one sample t-test known that comparison income clean month with the minimum wage districts semarang different real (P>0,05).Key words: Profitability Analysis, Layer Poultry, Revenue